Eculizumab‐related drug reaction in a patient with neuromyelitis optica. Issue 2 (8th February 2023) - Sharma, Rishi; Romo, Moises; Nelson, Flavia
Abstract: Eculizumab is approved for treatment of antibody positive neuromyelitis optica, myasthenia gravis, and hematologic disorders like paroxysmal nocturnal hemoglobinuria. Drug rash has not yet been reported as a side effect of eculizumab. We report a case of a cutaneous drug reaction soon after introduction of eculizumab therapy in a patient with refractory neuromyelitis optica. Clinicians should be aware of a drug reaction as a possible adverse reaction to eculizumab. Abstract :